Advances in Constitutive Relations Applied in Computer Codes - Klepaczko, Janusz R.; Lodygowski, Tomasz (CISM International Centre for Mechanical Sciences, Courses and Lectures,, 2009)
Many important industrial applications incline toward better understanding of the constitutive properties of matter. Nowadays, the development of measurement possibilities, even in nanoscale, allows for multiscale formulations that drive to the more sophisticated models used in continuum mechanics. These phenomenological models are particularly important and useful for solutions of very concrete initial boundary value problems. Our interests are focused mainly on detailed descriptions of material behavior that depend not only on simple stress-strain relationships but also includes the strong influence of loading type, which introduces temperature, strain rate dependence, fracture, etc. Understanding these physics phenomena is of fundamental importance for successful and responsible computations. In particular, using the popular commercial programs requires deep understanding of constitutive formulations and their restrictions. These lectures are addressed to industrial users who are responsible for making crucial decisions in design, as well as, to young scientists who work on new models that describe the behavior of materials which also account the new influences and reflect the complexity of the material behavior. At the end, let me express my gratitude to the lecturers of the CISM course No. 328 on "Advances in Constitutive Relations Applied in Computer Codes", held in Udine in July 2007, who finally prepared the included materials. Unfortunately, during the preparation and collecting papers for this book, our friend and colleague Prof. Janusz R. Klepaczko passed away. This is a very big loss for the society of mechanics.